A reflection on gaining work experience as a student: an uphill journey - Blake-Collins, Alivia (My University, 2022)
Reflecting on past learnings is an excellent way of understanding personal goals and overall self. This understanding is beneficial as it allows for individuals to conclude on decisions and better a variety of skills. The purpose of this critical reflection is to ponder on all experience, information, and skills gained throughout this university term. This process will be done using past journal entries and tasks demonstrating growth and personal opinions throughout this term, ultimately leading to conclusions on topics such as future employment goals. Throughout this term, I have narrowed my employment goals, broadened essential skills, and gained a detailed understanding of teamwork.
Keywords: work integrated learning; post-secondary education